PENGARUH MANAJEMEN LABA AKRUAL DENGAN PENDEKATAN REVENUE DISCRETIONARY MODEL DAN MANAJEMEN LABA RIIL TERHADAP NILAI PERUSAHAAN - Heni Yusnita (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
The purpose of this research aims to determine the effect of earnings management on firm value. Earnings management proxy by accrual activity with revenue discretionary model (Stubben 2010) and real activity with method Roychowdhury (2006), firm value meausured Price To Book Value. The population involved in this study were all the manufacture companies listed in the Indonesia stock exchange during 2015-2016. The samples were selected by using purposive sampling method. The analysis was conducted based on multiple linear regressions supported by SPSS program. The results show that the manufacturing companies listed in Indonesia Stock Exchange tend to execute accruals earnings management and real earnings management throught the operating cash flow . Moreover, accruals earnings management and real earnings management through operating cash flow have influence on firm value. The research is expected to be information for business people about the existence of accrual earnings management and real earnings management and its impact to firm value, so it can be a consideration in making investment decisions.